![image](https://tex.z-dn.net/?f=x%5E2-12x%2Bn%3D0%5C%5CD%3E0%5C%5Cx_1-x_2%3D2%5Csqrt%7B5%7D%5C%5C%5C%5CD%3D%28-12%29%5E2-4n%3D144-4n%5C%5C144-4n%3E0%5C%5C4n%3C144%5C%5Cn%3C36%5C%5C%5C%5Cx_%7B1%2C2%7D%3D%5Cfrac%7B12%D0%B1%5Csqrt%7B144-4n%7D%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7B12%2B%5Csqrt%7B144-4n%7D%7D%7B2%7D-%5Cfrac%7B12-%5Csqrt%7B144-4n%7D%7D%7B2%7D%3D2%5Csqrt%7B5%7D%7C%2A2%5C%5C%5C%5C12%2B%5Csqrt%7B144-4n%7D-12%2B%5Csqrt%7B144-4n%7D%3D4%5Csqrt%7B5%7D%5C%5C2%5Csqrt%7B144-4n%7D%3D4%5Csqrt%7B5%7D%7C%3A2%5C%5C%5Csqrt%7B144-4n%7D%3D2%5Csqrt%7B5%7D%5C%5C144-4n%3D20%5C%5C4n%3D124%5C%5Cn%3D31)
0\\x_1-x_2=2\sqrt{5}\\\\D=(-12)^2-4n=144-4n\\144-4n>0\\4n<144\\n<36\\\\x_{1,2}=\frac{12б\sqrt{144-4n}}{2}\\\\\frac{12+\sqrt{144-4n}}{2}-\frac{12-\sqrt{144-4n}}{2}=2\sqrt{5}|*2\\\\12+\sqrt{144-4n}-12+\sqrt{144-4n}=4\sqrt{5}\\2\sqrt{144-4n}=4\sqrt{5}|:2\\\sqrt{144-4n}=2\sqrt{5}\\144-4n=20\\4n=124\\n=31" alt="x^2-12x+n=0\\D>0\\x_1-x_2=2\sqrt{5}\\\\D=(-12)^2-4n=144-4n\\144-4n>0\\4n<144\\n<36\\\\x_{1,2}=\frac{12б\sqrt{144-4n}}{2}\\\\\frac{12+\sqrt{144-4n}}{2}-\frac{12-\sqrt{144-4n}}{2}=2\sqrt{5}|*2\\\\12+\sqrt{144-4n}-12+\sqrt{144-4n}=4\sqrt{5}\\2\sqrt{144-4n}=4\sqrt{5}|:2\\\sqrt{144-4n}=2\sqrt{5}\\144-4n=20\\4n=124\\n=31" align="absmiddle" class="latex-formula">